Muscular dystrophy model - Saranyapin Potikanond (2018)
© 2018, Springer Nature Singapore Pte Ltd. Muscular dystrophy (MD) is a group of muscle weakness disease involving in inherited genetic conditions. MD is caused by mutations or alteration in the genes responsible for the structure and functioning of muscles. There are many different types of MD which have a wide range from mild symptoms to severe disability. Some types involve the muscles used for breathing which eventually affect life expectancy. This chapter provides an overview of the MD types, its gene mutations, and the Drosophila MD models. Specifically, the Duchenne muscular dystrophy (DMD), the most common form of MD, will be thoroughly discussed including Dystrophin genes, their isoforms, possible mechanisms, and signaling pathways of pathogenesis.